2014
DOI: 10.3727/036012914x14109544776178
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Acupuncture Treatment on Nitric Oxide (NO) in Migraine Patients

Abstract: The purpose of this study is to contribute to efforts to understand the pathophysiology of migraine and create an alternative perspective for prophylaxis and treatment of migraine attacks. Acupuncture treatment was applied to the 22 volunteer migraine patients. The acupuncture treatment consists of 5 sessions with 2 sessions per week. Blood samples have been collected before performing acupuncture, after the 1st session and after the 5th session of the acupuncture. And for the control group blood samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Acupuncture could regulate some migraine-affected key regions as well as the pain circuitry of the brain and cognitive pain processing [52]. It was also shown to significantly decrease serum NO levels (a potent vasodilator contributing to headache) in migraine patients [53]. Acupuncture treatment could also significantly decrease matrix metalloproteinase-2 (MMP-2) activity in patients with migraine without affecting the MMP-2 concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture could regulate some migraine-affected key regions as well as the pain circuitry of the brain and cognitive pain processing [52]. It was also shown to significantly decrease serum NO levels (a potent vasodilator contributing to headache) in migraine patients [53]. Acupuncture treatment could also significantly decrease matrix metalloproteinase-2 (MMP-2) activity in patients with migraine without affecting the MMP-2 concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…[11] There are also studies showing the efficacy of acupuncture in reducing the number of migraine attacks. [12,13] Some authors also reported that acupuncture accelerated healing process, resolved edema, and provided analgesia in a case of metatarsal fracture. [14] In conclusion, to the best of our knowledge, this is the first case report to show the effectiveness of acupuncture in the treatment of venous insufficiency and varicose veins.…”
Section: Discussionmentioning
confidence: 99%
“…Lee and colleagues 23 have shown that carrageenan-induced expression of inducible nitric oxide synthase, which is known to generate nitric oxide, was inhibited by 2 Hz electro-acupuncture treatment in animals. It has also been shown that acupuncture treatment can progressively decrease the levels of serum NO in migraine patients 24 . As NO has been shown to be involved in vasodilatation, the finding for a decrease in nNO levels in the present study suggests that that SPG acupuncture may partly lead to decreased nasal congestion by attenuating NO-induced vasodilation and subsequent swelling of the nasal mucosa.…”
Section: Discussionmentioning
confidence: 99%